Przestępstwo publicznego propagowania faszystowskiego lub innego totalitarnego ustroju państwa (art. 256 k.k.). Analiza doktrynologiczna wybranych wypowiedzi piśmiennictwa i judykatury. Część szczególna III - Scheffler, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The paper presents interpretations of the content of art. 256 of the Polish Penal Code of 1997 (The crime of public propagation of a fascist or other totalitarian governmental/state system), which were developed amid amendment in 2009. The most difficult problem for commentators, much like authors, about whom we have deliberated earlier, was to understand the complexity of the phenomenon of totalitarianism and the consequences resulting from accepting one of the competing concepts of totalitarianism. Similarly, interpretational problems led to misunderstandings of the concept of fascism and the state system. As a result, individual authors incorrectly found resemblance between the regulations contained in the Penal Code of 1969 and the regulation contained in art. 256 from 1997. In this paper we prove that the Polish Supreme Court and even Polish Constitutional Tribunal also had the same problem with the interpretation of the content of art. 256.
Keywords: totalitaryzm; faszyzm; kodeks karny